Dental palliative care for patients with oral cancer (Research, Society and Development, 2023)
It is known that the quality of an individual's oral health is extremely important, and future damage such as periodontal disease and recurrent caries should be prevented. Individuals who are undergoing palliative cancer treatments have several systemic problems. The objective of this work is to highlight the importance of palliative dental care in patients with oral cancer, both for patients and their families. This is a narrative review of descriptive and qualitative literature available in the online databases PubMed, Google Scholar, Scielo and Lilacs, and articles published between 2005 and 2022 in Portuguese and English were selected. Oral diseases such as xerostomia, candidiasis and stomatitis are highly prevalent in patients with serious diseases, which can lead to complications and compromise the quality of life of these patients. For this reason, care by dentists is extremely important, as the individual's oral health affects the systemic condition, especially in palliative patients. Palliative care seeks to provide a better quality of life for both patients with advanced disease and support their families for as long as necessary. It is concluded, therefore, that palliative care is extremely important for cancer patients, regardless of whether they are in a hospital environment or not.